Assessment of changes in optic disc parameters and peripapillary retinal nerve fiber layer thickness in myopic patients and its correlation with axial length and degree of myopia - Alpana Mishra; Lolly Pattnaik; Suchismita Mishra; Pradeep Kumar Panigrahi; Smaraki Mohanty (Indian Journal of Ophthalmology, 2022)
Purpose: The present study aimed to assess the changes in optic disc and peripapillary retinal nerve fiber layer (RNFL) parameters in myopic patients and its correlation with axial length (AL) and spherical equivalent (SE) using optical coherence tomography (OCT). Methods: This was a cross-sectional study carried out from August 2019 to September 2021 in the ophthalmology department of a tertiary care hospital in eastern India. Myopic patients in the age group of 20–40 years and SE between − 0.5 to − 10 Diopters (D) were included in the study. Patients were divided into two groups on the basis of degree of myopia and AL. Appropriate statistical analysis was done at the end of the study period. Results: The study included 307 eyes of 307 myopic patients. There were 181 females (58.96%) and 126 males (41.04%). The mean age of the patients enrolled for the study was 28.78 ± 5.76 years. Statistically significant difference (P < 0.001) was found between SE and AL in between the subgroups of A and B. With every 1 D increase in SE, the average peripapillary RNFL thickness decreased by 0.61 μ while with every 1 mm increase in AL, the average peripapillary RNFL thickness was found to reduce by 1.03 μ. Conclusion: Analysis of optic nerve head parameters and RNFL thickness by OCT for the diagnosis should be compared with a normative control group that has been matched for refractive error and AL instead of comparison with a normative database that has only been age matched.